1999
DOI: 10.2134/jeq1999.00472425002800050008x
|View full text |Cite
|
Sign up to set email alerts
|

Organic Waste Amendments Effect on Zinc Fractions of Two Soils

Abstract: Organic soil amendments can ameliorate metal toxicity to plants by redistributing metals to less available fractions. The objective of this study was to determine the effects of organic amendments on Zn distribution among soil fractions. Two soils (fine‐textured and coarse‐textured) were amended with five organic waste materials (some of which contained Zn) or commercial humic acid with and without 400 mg kg−1 Zn, incubated, and fractionated using a sequential extraction technique. Where no Zn was added most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
90
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(106 citation statements)
references
References 0 publications
9
90
0
7
Order By: Relevance
“…Zinc, as the most common micronutrient deficiency in the Pacific Northwest, is generally applied annually (Peryea 2006). Biosolids frequently have high Zn concentrations and the potential to alter Zn availability in the soil (Shuman 1999). Although the effects of biosolids application on micronutrient concentrations of agronomic crops has been documented (Shober et al 2003), there is much less information available for fruit trees, despite a potential for ameliorating inadequate Zn concentrations.…”
mentioning
confidence: 99%
“…Zinc, as the most common micronutrient deficiency in the Pacific Northwest, is generally applied annually (Peryea 2006). Biosolids frequently have high Zn concentrations and the potential to alter Zn availability in the soil (Shuman 1999). Although the effects of biosolids application on micronutrient concentrations of agronomic crops has been documented (Shober et al 2003), there is much less information available for fruit trees, despite a potential for ameliorating inadequate Zn concentrations.…”
mentioning
confidence: 99%
“…The decrease in the levels of Cu and Zn with N application through the deep litter were probably due to complexation and/or by chelatization of organic matter, organic compounds of low and high molecular weight (SHUMAN, 1999), with low availability to corn plants due to the reduced trial period for digestion of the deep litter. SILVA et al (2007) evaluated the effects of the application of municipal solid waste, or not enriched with heavy metals, in the cultivation of sugarcane and concluded that Cu is an element of concern, since it is very mobile and has high speed of passage, if not immobilized in soil organic matter.…”
Section: **Significative At 1% By the T Test Averages Followed By Thmentioning
confidence: 99%
“…In most cases, the organic material to a lesser extent affects the availability of Fe and Mn in the Zn and especially to Cu. On the other hand, with larger dosages may be CSS complexation of Fe and Mn containing organic compounds of high molecular weight (humic substances) of more stable forms with these metals (SHUMAN 1999).…”
Section: **Significative At 1% By the T Test Averages Followed By Thmentioning
confidence: 99%
“…Almost all elements that are essential are, however, injurious at elevated amounts [14]. Practically, all toxic elements have impacts on multiple organ systems with biochemical processes and/or organelles as targets.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, all toxic elements have impacts on multiple organ systems with biochemical processes and/or organelles as targets. The toxicity of metals frequently harms brain and kidney; they are capable of causing other diseases such as cancer, anemia, hypertension, general weakness of the body, and headache [14,15].…”
Section: Introductionmentioning
confidence: 99%